Petis and Madurese Cultural Identity - Nikmah Suryandari; Qoniah Nur Wijayani (Universitas Muhammadiyah Sidoarjo, 2020)
The purpose of this study was to determine the relationship between people with food, which can reveal a lot of information about them. The choice of food is able to expose a group or a person's belief, passion, background knowledge, assumptions and personality. food choices and eating habits understood to be related to the phenomenon of socialization and social bonding, the construction of collective identity under which to show the logic of social distinction and organization of life in society.